The Multisensory Driver: Implications for Ergonomic Car Interface Design - Ho, Cristy; Spence, Charles (Human factors in road and rail transport, 2008)
This book is dedicated to furthering the design of ergonomic multisensory interfaces by highlighting recent evidence in this area emerging from the fast-growing field of cognitive neuroscience. It focuses primarily on two aspects of driver information-processing: multisensory interactions and the spatial distribution of attention in driving.